Active periodic electrograms in remote monitoring of pacemaker recipients: the PREMS study. Issue 1 (27th June 2018) - Lazarus, Arnaud; Guy-Moyat, Benoit; Mondoly, Pierre; Pons, Frédéric; Quaglia, Carlo; Elkaim, Jean-Philippe; Bayle, Sandrine; Victor, Frédéric
Abstract: Aims: Remote monitoring (RM) is considered as a standard of care for pacemaker recipients. Remote monitoring systems provide calendar-based intracardiac electrogram recordings (IEGM) only with the current pacemaker settings (passive IEGM). PREMS (Pacemaker Remote Electrogram Monitoring Study), an observational, multicentre trial, prospectively evaluated the clinical value of an active IEGM (aIEGM), including three 10-s sections (passive IEGM, encouraged sensing, and encouraged pacing), compared to other RM data and to its passive IEGM section. Secondary objectives included the added value of the aIEGM to fully assess the sensing and pacing functions of each lead. Methods and results: Patients were enrolled within 3 months after pacemaker implantation and followed until the first transmitted aIEGM, which was analysed together with all other RM data. In total, 567 patients were enrolled (79 ± 9 years, 62% men, 19% single-chamber, and 81% dual-chamber pacemakers). Of 547 aIEGMs transmitted in 547 patients, 161 [29.4%; 95% confidence interval (95% CI) 25.6–33.3%] indicated at least one anomaly non-detectable with certainty—or at all—on other RM data, including atrial arrhythmia, extrasystoles, undersensing, oversensing, and loss of capture. In 21.7% of cases the detected events deserved a corrective action. The sensing and pacing function of each lead could be fully assessed in 77.3% of aIEGM (95% CI 72.6–82.0%) vs. 15.5% (95% CI 11.4–19.6%) when considering only the passive IEGM section ( P <  0.001). Conclusion: An active IEGM improves the clinical value of remote pacemaker follow-up. Furthermore, compared to a passive IEGM, the aIEGM increases the capability to fully assess remotely the sensing and pacing functions.